2019
DOI: 10.1186/s12711-019-0479-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genomic regions underlying resistance to gastrointestinal parasites in Australian sheep

Abstract: Background This study aimed at identifying genomic regions that underlie genetic variation of worm egg count, as an indicator trait for parasite resistance in a large population of Australian sheep, which was genotyped with the high-density 600 K Ovine single nucleotide polymorphism array. This study included 7539 sheep from different locations across Australia that underwent a field challenge with mixed gastrointestinal parasite species. Faecal samples were collected and worm egg counts for three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 60 publications
(67 reference statements)
3
39
1
3
Order By: Relevance
“…Several overlapping genes related to innate and adaptive immunity in mammals, such as HERC2 and CYFIP1 , were identified in this study, which are reported to regulate innate and acquired immune response, as well as cytokine signaling. In addition, HERC2 and CYFIP1 , which are involved in hemostasis regulation and mucosal defense, are also detected, which are of great significance in protecting sheep from parasites [ 67 ]. Furthermore, HERC2 is a marker gene reported for biological predictions, some of which are unique and need functional verification [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several overlapping genes related to innate and adaptive immunity in mammals, such as HERC2 and CYFIP1 , were identified in this study, which are reported to regulate innate and acquired immune response, as well as cytokine signaling. In addition, HERC2 and CYFIP1 , which are involved in hemostasis regulation and mucosal defense, are also detected, which are of great significance in protecting sheep from parasites [ 67 ]. Furthermore, HERC2 is a marker gene reported for biological predictions, some of which are unique and need functional verification [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several overlapping genes involved in regulating innate and adaptive immunity in mammals were identified; for example, HERC2 and CYFIP1 genes that are relevant to regulate innate and acquired immune responses, as well as cytokine signaling [54]. Multiples candidate genes were also found to participate in host defense mechanism, resistance diseases, and inflammatory responses, with two most significant genes worth to mention as examples.…”
Section: Candidate Genes Related To Immune Response and Disease Resismentioning
confidence: 99%
“…This indirect preference for such individuals may be responsible for this selection signal. SOCS2 has also been reported to play important roles in key adaptive phenotypes in sheep, including general immune response following infection ( Yang et al, 2015 ; Al Kalaldeh et al, 2019 ) and resistance to gastrointestinal nematode ( Haemonchus contortus ) ( Estrada-Reyes et al, 2019 ). The proteasome PSMB7 and the heat shock protein HSPA5 , both found in the region on OAR3, were reported to be upregulated during blastocyst implantation in hamsters ( Lei et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%